2019
DOI: 10.1002/advs.201900295
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Binding Protein IGF2BP2/IMP2 is a Critical Maternal Activator in Early Zygotic Genome Activation

Abstract: A number of genes involved in zygotic genome activation (ZGA) have been identified, but the RNA‐binding maternal factors that are directly related to ZGA in mice remain unclear. The present study shows that maternal deletion of Igf  2bp2 (also commonly known as Imp2 ) in mouse embryos causes early embryonic developmental arrest in vitro at the 2‐cell‐stage. Transcriptomics and proteomics analyses of 2‐cell‐stage embryos in mice reveal that deletion of IMP2 downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 62 publications
4
58
0
Order By: Relevance
“…In addition, miR-670-3p was found to regulate IGF2BP1 and affect apoptosis in PA embryos ( Hao et al, 2020 ). Subsequently, Liu H.B. et al (2019) reported that IGF2BP2 (also known as IMP2) is highly expressed in oocytes and early-stage embryos.…”
Section: A Modification and Mammalian Embryonimentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, miR-670-3p was found to regulate IGF2BP1 and affect apoptosis in PA embryos ( Hao et al, 2020 ). Subsequently, Liu H.B. et al (2019) reported that IGF2BP2 (also known as IMP2) is highly expressed in oocytes and early-stage embryos.…”
Section: A Modification and Mammalian Embryonimentioning
confidence: 99%
“…et al (2019) reported that IGF2BP2 (also known as IMP2) is highly expressed in oocytes and early-stage embryos. IGF2BP2 deletion was not essential for oocyte maturation, while IGF2BP2-knockout mice exhibited female infertility ( Liu H.B. et al, 2019 ).…”
Section: A Modification and Mammalian Embryonimentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition of m 6 A mRNA by YTHDF2 within the GACU/A consensus is associated with mRNA destabilization and degradation (Du et al, 2016), suggesting that maternal mRNA clearance is also under the tight control of m 6 A. Indeed, an increasing number of studies demonstrated that knockout of IGF2BP2 (Liu et al, 2019), YTHDC2 (Hsu et al, 2017), and YTHDF2 (Zhao et al, 2017) impaired maternal mRNA elimination. Moreover, zygotic transcription is first detected at the late 1-cell stage, whereas the majority of maternal mRNAs are removed by the 2-cell stage in mice (Sha et al, 2019a;Vastenhouw et al, 2019), suggesting that there is a complex crosstalk of maternal and zygotic products in regulating MZT, thus ensuring timely transfer of developmental control (Sha et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%